A novel snail-inspired bionic design of titanium with strontium-substituted hydroxyapatite coating for promoting osseointegration. (20th July 2021) - Geng, Zhen; Li, Xueping; Ji, Luli; Li, Zhaoyang; Zhu, Shengli; Cui, Zhenduo; Wang, Jing; Cui, Jingyuan; Yang, Xianjin; Liu, Changsheng
Graphical abstract: Highlights: Titanium was functionalized by bionic micro/nano-structure and Sr-HA coating. Functionalized titanium could promote cell adhesion and inhibit osteoclast activity. Functionalized titanium could improve the bone-implant bonding strength. Abstract: As the population ages, more and more people are suffering from osteoarthritis (OA), resulting in an increasing requirement for joint implants. Surface modification to improve the topology and composition of the implants has been proved to be an effective way to improve the primary stability and long-term success rate of joint implants. In this work, a bionic micro/nano-structure accompanied with a strontium-substituted hydroxyapatite (SrHA) coating was fabricated on titanium (Ti) surface via electrochemical corrosion, ultrasonic treatment, and hydrothermal deposition methods. The in vitro study demonstrated that the bionic structure and the bioactive apatite could synergistically increase the expressions of integrin-related gene (ITG α5β1) and osteoblastic genes (Col-I and OCN), and thus promote osteoblast growth. In addition, owing to the anti-bone resorption property of Sr 2+, the coating could effectively inhibit osteoclast differentiation and proliferation. In a word, the prepared samples not only promoted osteogenesis but also inhibited osteoclastogenesis. The in vivo experiment via a rabbit model found that the bionic structured surface provided the pore for new bone ingrowth, which was beneficial to the mechanical interlocking between the implant and bone. Moreover, the bionic structure and bioactive SrHA coating had a synergistic effect on promoting bone formation, osseointegration, and bone-implant bonding strength. This study therefore presented a new strategy to fabricate bio-functionalized Ti-based implants for potential application in orthopedics field.